Neurochemistry of consciousness : neurotransmitters in mind - Perry, E. K. (Elaine K.); Ashton, Heather; Young, A. H. (Allan H.) (Advances in consciousness research, 2002)
This pioneering book explores in depth the role of neurotransmitters in conscious awareness. The central aim is to identify common neural denominators of conscious awareness, informed by the neurochemistry of natural, drug induced and pathological states of consciousness. Chemicals such as acetylcholine and dopamine, which bridge the synaptic gap between neurones, are the 'neurotransmitters in mind' that form the substance of the volume, which is essential reading for all who believe that unravelling mechanisms of consciousness must include these vital systems of the brain. Up-to-date informati.